2010
DOI: 10.1111/j.1745-4573.2010.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF ADDED CRUDE GREEN TEA POLYPHENOL ON THE LIPID OXIDATION OF COMMON CARP (CYPRINUS CARPIO L.) AND CATFISH (CLARIAS GARIEPINUS BURCHELL) DURING REFRIGERATED STORAGE

Abstract: The antioxidant activity of crude green tea polyphenol (GTP) on the lipid oxidation of carp (Cyprinus carpio L.) and catfish (Clarias gariepinus Burchell) was investigated. Each fish was trimmed to remove scales, head, fins, tail, viscera, bones, visible fat and skin, and treated with different concentrations of GTP 0.01, 0.03, 0.05 and 0.01% of vitamin C (VC). Control muscle sample (CK) contained no antioxidant. Lipid oxidation was evaluated over a course of 9 days and using a 3-day periodical interval analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…Similar to our fi ndings, these acids were reported to be the predominant fatty acids in common carp [Trbović et al, 2013]. In contrast, Dembele et al [2010] and Pirestani et al [2010] found other dominant acids among PUFA, i.e. C18:3n-6, as well as DHA and EPA, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our fi ndings, these acids were reported to be the predominant fatty acids in common carp [Trbović et al, 2013]. In contrast, Dembele et al [2010] and Pirestani et al [2010] found other dominant acids among PUFA, i.e. C18:3n-6, as well as DHA and EPA, respectively.…”
Section: Resultssupporting
confidence: 89%
“…The TBA value of the fresh carp fi llet in this study was higher than was the value reported for the muscle tissue of the carp (0.345 MDA/kg tissue) that had a higher lipid fat content (2.61%) [Dembele et al, 2010], and similar to that reported for mangar (Luciobarbus esocinus) fi llet (0.59 mg MDA/kg tissue), with a lipid content of 6.23%. Likewise, it is also similar to the farmed brown trout fi llet (0.65 mg MDA/kg), with a lipid content of 3.16% [Dal Bosco et al, 2013].…”
Section: Resultssupporting
confidence: 68%
“…TBARS value (mg MDA kg −1 wet muscle) was determined by the method described previously . Briefly, 0.5 g samples was blended with 2.5 mL of 0.375% TBA–15% TCA–0.25 mol L −1 HCl stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, chemical preservatives such as hydrogen peroxide and chlorine dioxide have been widely used to keep the fish fresh and mitigate the deleterious effects of spoilage. However, potential harm to human health cannot be ignored if the intake of these applications exceeds acceptable levels . In recent years, increasing attention has been paid to developing natural preservatives for the preservation of large yellow croaker, such as tea polyphenols and rosemary extract …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation